Estruturas secretoras de Pavonia alnifolia (Malvaceae), uma espécie ameaçada de extinção - Pimentel, Rafael Ribeiro; Machado, Silvia Rodrigues [UNESP]; Rocha, Joecildo Francisco (Instituto de Pesquisas Jardim Botânico do Rio de Janeiro, 2011)
Malvaceae shows a rich morphological diversity of secretory structures, which are of great ecological and taxonomical relevance. Nonetheless, until the present moment, studies on the secretory structures of the studied species were not found. Pavonia alnifolia A.St.-Hil. is endangered species of extinction with restricted distribution within the restingas of Rio the Janeiro and Espírito Santo, Brazil. The species were collected from the former and usual techniques on plant anatomy and histochemistry were performed. Anatomical and histochemical studies of the secretory structures of Pavonia alnifolia are showed in this work. The presence of external and internal secretory structures of mucilage in many organs, idioblasts of phenolic and lipid substances and floral nectaries what is a very important adaptative survival mechanism of the species in the restinga environment. The secretion produced by nectaries is envolved with maintenance of interations with visiting insects, what constitutes a good model to experimental studies with an ecological approach.

Malvaceae possui grande diversidade morfológica de estruturas secretoras, que por sua vez apresentam importância ecológica e taxonômica. Entretanto até o momento não foram encontrados registros de estudos sobre as estruturas secretoras em Pavonia alnifolia A.St.-Hil., uma espécie ameaçada de extinção, endêmica de restingas do Rio de Janeiro e Espírito Santo. No presente estudo são apresentados dados anatômicos e histoquímicos das estruturas secretoras da referida espécie. O material foi coletado na Restinga da Marambaia - Rio de Janeiro e processado de acordo com técnicas usuais para estudos de anatomia e histoquímica. A análise dos resultados mostrou a presença de canais, cavidades, idioblastos e tricomas secretores de mucilagem; idioblastos de substâncias fenólicas e lipídicas, além de nectários florais. As secreções produzidas por estas estruturas representam um papel potencialmente importante para adaptação da espécie ao ambiente de restinga, estando envolvidas na manutenção de interações com insetos visitantes, o que constitui relevante modelo para realização de estudos experimentais com abordagem ecológica.
Secretory structures in Pavonia alnifolia (Malvaceae), an endangered species of extinction
Keywords: anatomy; histochemistry; secretory structures; Marambaia; Pavonia; anatomia; estruturas secretoras; restinga; Marambaia; Pavonia